1989
DOI: 10.1093/oxfordjournals.eurheartj.a059507
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic epidural anaesthesia in patients with unstable angina pectoris

Abstract: The effect of high thoracic epidural anaesthesia with intermittent epidural bolus injections of bupivacaine (2.5 or 5 mg ml-1) was studied in 28 patients with unstable angina pectoris. The majority of the patients had a history of previous acute myocardial infarction(s) and/or angina pectoris and severe coronary artery disease. All patients were treated with nitroglycerin infusion for greater than 24 h and were included in the study if they had chest pain, not caused by acute myocardial infarction, at bed rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(23 citation statements)
references
References 0 publications
1
20
0
1
Order By: Relevance
“…In dogs subjected to myocardial infarction, thoracic epidural analgesia has been shown to reduce myocardial infarct size by nearly 50%, to reduce myocardial oxygen consumption and to improve endocardial perfusion [10]. In patients with unstable angina, thoracic epidural analgesia has been used not only to relieve angina but also to reduce systemic and pulmonary arterial pressure without significantly affecting coronary perfusion pressure, cardiac output or stroke volume [11,12]. In vascular surgery, epidural analgesia may improve vascular graft patency by a variety of mechanisms such as increased blood flow, a reduction in platelet reactivity, increased fibrinolysis and haemodilution [13], all of which may be relevant to patients undergoing coronary grafting.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs subjected to myocardial infarction, thoracic epidural analgesia has been shown to reduce myocardial infarct size by nearly 50%, to reduce myocardial oxygen consumption and to improve endocardial perfusion [10]. In patients with unstable angina, thoracic epidural analgesia has been used not only to relieve angina but also to reduce systemic and pulmonary arterial pressure without significantly affecting coronary perfusion pressure, cardiac output or stroke volume [11,12]. In vascular surgery, epidural analgesia may improve vascular graft patency by a variety of mechanisms such as increased blood flow, a reduction in platelet reactivity, increased fibrinolysis and haemodilution [13], all of which may be relevant to patients undergoing coronary grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Davis et al (3 1) have demonstrated that cardiac sympathetic blockade with TEA during coronary occlusion decreases myocardial infarction size in anaesthetized dogs. Furthermore, Blomberg et al (40) and Tevelenok et al (19) showed that high TEA, involving blockade of cardiac sympathetic segments, induced a fall in MAP of less than 10% in patients with unstable angina pectoris (40) and acute myocardial infarction (19). If so, the anti-arrhythmic effect of TEA may be explained by a decrease in severity of the ischaemic insult.…”
Section: Discussionmentioning
confidence: 99%
“…This might be of importance if, for example, early intervention with thoracal epidural blockade should take place [8]. The possibil ity to predict the severity of pain was further evaluated in two subsequent studies a few years ago [2,3].…”
Section: Subgroup Analysesmentioning
confidence: 99%